Enzymoimunologické stanovení mykotoxinu ochratoxin A - Ruprich, J; Ostrý, V (Veterinarni medicina, 1991)
Indirect, enzymoimmunological assays of the mycotoxin ochratoxin A were developed. In this technique a polyclonal (rabbit) antibody to ochratoxin A was used, along with the other, peroxidase-labelled (pig anti rabbit) antibody. The sensitivity of this method ranged around 75 pg of ochratoxin A per pit. The range of calibration curve was from 10 to 1000 pg per pit. The cross reactions with other ochratoxins made 1.4% (ochratoxin C). The ELISA test of ochratoxin A can be used as an expeditious screening method for a preliminary examination of the greater number of samples.
Keywords: Ochratoxins; ochratoxiny; Enzyme-Linked Immunosorbent Assay; ELISA